INCLUSIVE EDUCATION FOR STUDENTS WITH DISABILITIES - Dosmambetova Muyassar (Western European Studies, 2025)
Inclusive education has emerged as a critical paradigm in the field of education, promoting the integration of students with disabilities into mainstream classrooms. This article reevaluates the principles, practices, and challenges of inclusive education, emphasizing its significance in fostering social equity and academic success. It explores historical contexts, legislative frameworks, pedagogical strategies, and the roles of educators and families in creating an inclusive environment. The discussion highlights the need for ongoing professional development and collaboration among stakeholders to address barriers and enhance the quality of education for all students.
Keywords: Inclusive education; students with disabilities; social equity